(untitled) (Journal of Geography and Environmental Management, 2023)
The role of snowmelt is of great importance in the spring, when temperature drops pass, and with them the transformation of snow into water. The melting process takes several weeks. With a sharp warming, the rapid melting of snow can lead to abundant floods. In Kazakhstan, in recent decades, floods have caused damage of republican significance and are considered large-scale. Knowing the parameters and characteristics of the snow cover, as well as predicting and modeling the passage of floods, is essential for preventing large-scale disasters. The use of Earth remote sensing data, in particular the study of snow cover over many years, made it possible to assess the accuracy of the passage of floods. In Kazakhstan, in the last decade, the air temperature has increased by an average of 1-4 C. In this regard, the cases of heavy floods in the regions of Central and Northern Kazakhstan was observed. An important factor in modeling the passage of floods is the factor of water absorption (infiltration) by frozen soil. The analysis of data on frozen soil is mainly carried out by ground and field, as well as laboratory studies. This article is devoted to a retrospective analysis of optical and radar images in order to identify areas of snow cover compaction and the appearance of ice over the soil. According to optical images in the spring, areas with a presumable characteristic of icing were selected. Further, various combinations of polarization VH-VV, VV-VH, VV, HH Sentinel 2 Satellite were downloaded from radar images to these areas, for which an analysis of the regression dependence of the signal display in dark and light areas of the image was carried out. The analysis carried out in the work shows different areas of dispersion, where there is a difference in the composition of snow and ice content in the composition. However, this method does not allow to analyze the depth of soil freezing.